Partial Identification of the Long-Run Causal Effect of Food Security on Child Health - Daniel L. Millimet; Manan Roy (Institute for the Study of Labor (IZA), 2013)
Food security and obesity represent two of the most significant public health issues. However, little is known about how these issues are intertwined. Here, we assess the causal relationship between food security during early childhood and relatively long-run measures of child health. Identifying this causal relationship is complicated due to endogenous selection and misclassification errors. To overcome these difficulties, we utilize a nonparametric bounds approach along with data from the ECLS-K and ECLS-B. The analysis reveals a positive association between food insecurity and future child obesity in the absence of misclassification. However, under relatively innocuous assumptions concerning the selection process, we often obtain bounds that indicate a negative causal effect of food insecurity on future child obesity. All results are extremely sensitive to misclassification.
Keywords: C14; C21; I12; I32; 330; food insecurity; health outcomes; nonclassical measurement error; nonparametric bounds